Metod för användning av Geografiska Informations System vid långsiktig vägplanering - Thörnevall, Dan (2007)
The forest industry is one of the most important industry branches in Sweden. Since the demand of high precision wood deliveries has increased, the demand on a well constructed forest road net also has increased. A good road net gives the wood-supplier competition advantages and also increases its service level towards its customers, lumber-mills and pulp-mills. In some parts of Norrbotten, the road net is still insufficient and not yet built out enough, and that is why it is important to know how to act and where to improve the road net in these areas. The purpose of this thesis was to create a work-model for long term road planning in areas with no road net or a not yet complete road net. The model has been created in an ArcGis environment, where a long chain of tools has been tied together with the program "Model builder". High stock concentration in combination with long terrain transport distance means great necessity of roads. The areas with the biggest necessities get the highest prior for road-building, and a road proposal is drawn to every such area. A road proposal is drawn to every area that is considered to be in great need of roads. The ground characteristics rule the choice of where the road building should be done to reach the actual area to the lowest cost. The ground characteristics that are considered are carrying capacity, ground moist and slope. The road building that is totally the best considered to the different ground characteristics is the one that will be drawn. The road proposals are not allowed to cross nature reserves, national parks or any other forest that are kept for ecological purposes. The model was tested on three areas: Älvsbyn, Harads-Jokkmokk and Kalix inland. The tests showed that the model suggests more road-building in less built-out areas. The results also showed a few types of errors in the output data. The most important error that occurred was that roads could be drawn to areas that in fact were difficult to build roads in, for example steep slopes. That is because ...